2016
DOI: 10.1002/btpr.2350
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic tools toward industrial biotechnology

Abstract: Microfluidics is a technology that operates with small amounts of fluids and makes possible the investigation of cells, enzymes, and biomolecules and encapsulation of biocatalysts in a greater variety of conditions than permitted using conventional methods. This review discusses technological possibilities that can be applied in the field of industrial biotechnology, presenting the principal definitions and fundamental aspects of microfluidic parameters to better understand advanced approaches. Specifically, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 179 publications
0
22
0
Order By: Relevance
“…A complementary way to evaluate the microbial phenotypic heterogeneity under realistic bioprocess conditions is by employing scale down single cell micro-cultivation devices in which large scale reactors conditions are mimicked. Single cells in lab-on-a-chip microfluidic devices allow parallelization and high throughput experiments ( Grünberger et al, 2014 ; Dusny and Schmid, 2015 ; Rosenthal et al, 2015 ; Oliveira et al, 2016 ), contributing to large-scale bioprocess improvement ( Grünberger et al, 2012 ; Ladner et al, 2017 ). Sorting of different subpopulations of cells in order to understand the physiological responses in fluctuating microenvironments was also performed by microarray analysis ( Hewitt et al, 2007 ).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A complementary way to evaluate the microbial phenotypic heterogeneity under realistic bioprocess conditions is by employing scale down single cell micro-cultivation devices in which large scale reactors conditions are mimicked. Single cells in lab-on-a-chip microfluidic devices allow parallelization and high throughput experiments ( Grünberger et al, 2014 ; Dusny and Schmid, 2015 ; Rosenthal et al, 2015 ; Oliveira et al, 2016 ), contributing to large-scale bioprocess improvement ( Grünberger et al, 2012 ; Ladner et al, 2017 ). Sorting of different subpopulations of cells in order to understand the physiological responses in fluctuating microenvironments was also performed by microarray analysis ( Hewitt et al, 2007 ).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Microfluidic devices allow to conduct small-population or even single-cell cultivation. They have been applied to study growth under controlled conditions [72][73][74][75][76], and to study enzyme dynamics during slow extra-cellular variations [77,78], but not to impose rapid fluctuations (to our knowledge). Convective flow can renew volumes in less than a second in typical micro-cultivations, and with a diffusion coefficient = × − 6 10 m /s…”
Section: Towards Novel Scale Down Simulatorsmentioning
confidence: 99%
“…Regarding the applications of microbioreactors within industrial bioprocesses and fermentations, such results thus indicate the great potential of an unexplored research field. Furthermore, Oliveira et al (2016) carried out an analogous search concerning microfluidic approaches. Their study reported the availability of untouched possibilities for research not only for the application of microbioreactors in bioprocesses but also the general approaches of microfluidics in industrial biotechnology.…”
Section: The Origins Of Microbioreactorsmentioning
confidence: 99%
“…Their study reported the availability of untouched possibilities for research not only for the application of microbioreactors in bioprocesses but also the general approaches of microfluidics in industrial biotechnology. Regardless of the rapid growth of this field of study, microfluidics has been a subject of concern from specific engineering journals, denouncing the complexity found when applying such technology to various other fields of study or handled by non-experts (Oliveira et al, 2016).…”
Section: The Origins Of Microbioreactorsmentioning
confidence: 99%